Determining the effect of service quality towards patients' satisfaction in private hospitals in Kota Kinabalu, Sabah Malaysia / Sharifah Nurafizah Syed Annuar and Nur Shahafiqah Nadiah Jaffery - Syed Annuar, Sharifah Nurafizah; Jaffery, Nur Shahafiqah Nadiah (Universiti Teknologi MARA, Cawangan Melaka, 2018)
Intense competition in health care industry has resulted in increasing pressure among private hospitals to provide high quality services. In Sabah, the number of private hospitals is on the rise particularly when the state government has announced its strategic plan to become a medical tourism hub by offering medical treatments to the neighbouring countries. So far, there is not much studies can been found to measure the service quality in private hospitals in Sabah. Hence, the aim of this study is to determine the relationship between service quality and patients’ satisfaction among outpatients in the private hospitals in Kota Kinabalu, Sabah Malaysia. A cross-sectional study was carried out between March and April 2018 in Kota Kinabalu, Sabah Malaysia. The study sample was composed of 150 outpatients randomly selected from 5 private hospitals in Kota Kinabalu, Sabah, Malaysia. Data collected from this study were analysed using IBM SPSS Statistics 23.0 and Smart PLS-SEM 3.0. The findings show assurance and tangibility are positively correlated to patients’ satisfaction. Of the two important dimensions, tangibility demonstrated greater effect towards patients’ satisfaction. This study contributes to the service quality literature by testing the effect of the SERVQUAL dimensions to the patients’ satisfaction in the context of private hospitals. In addition, this paper is significant to practitioners specifically hospital managers in improving their serve delivery.